2014
DOI: 10.3892/ijo.2014.2702
|View full text |Cite
|
Sign up to set email alerts
|

Potent tumor tropism of induced pluripotent stem cells and induced pluripotent stem cell-derived neural stem cells in the mouse intracerebral glioma model

Abstract: Although neural and mesenchymal stem cells have been well-known to have a strong glioma tropism, this activity in induced pluripotent stem cells (iPSCs) has not yet been fully studied. In the present study, we tested tumor tropic activity of mouse iPSCs and neural stem cells derived from the iPSC (iPS-NSCs) using in vitro Matrigel invasion chamber assay and in vivo mouse intracranial tumor model. Both iPSC and iPS-NSC had a similar potent in vitro tropism for glioma conditioned media. The migrated iPSCs to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Our studies indicate that ipNSCs and hiPNSCs secreting S‐TRAIL have strong anti‐tumor capacity, suggesting their resemblance to already existing NSC‐based therapies . These findings are generally in coherence with the findings of others . However, our studies are the first to demonstrate that combined expression of S‐TRAIL and HSV‐TK by sECM encapsulated NSCs generated from iPSCs have anti‐tumor efficacy in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…Our studies indicate that ipNSCs and hiPNSCs secreting S‐TRAIL have strong anti‐tumor capacity, suggesting their resemblance to already existing NSC‐based therapies . These findings are generally in coherence with the findings of others . However, our studies are the first to demonstrate that combined expression of S‐TRAIL and HSV‐TK by sECM encapsulated NSCs generated from iPSCs have anti‐tumor efficacy in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…We and others have previously shown that NSC and MSC migrate extensively toward tumors and therefore have an enormous therapeutic potential as gene delivery vehicles 4347 . Most of the cancer cell lines used in this study were specifically chosen based on their unresponsiveness to death receptor agonist, TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the iPSCs did not differentiate during migration. These findings suggest that iPSCs and their derivatives can be feasible candidates as vehicles in stem cell-based gene therapy for brain tumors (Yamazoe et al, 2015).…”
Section: Stem Cell Homing and Migrationmentioning
confidence: 99%